Análise multitemporal do uso e cobertura do solo da Ilha de Cotijuba, Belém - PA - GAMA, Claudomiro da Gama e (2022)
Geoprocessing offers several possibilities for analyzing and monitoring environmental data, supporting decision-making with greater efficiency. Thus, this work aims to analyze the changes that occurred on the island of Cotijuba, between the 1990s, 2000, 2010 and 2022, through image processing from the Landsat 5, Landsat 8 and Sentinel 2 satellites. The results were constructed with based on the application of unsupervised Classification techniques associated with field surveys for data adjustments and the completion of a questionnaire. Over the period analyzed, there was a loss of vegetation cover and growth of the urbanized area on the island. The correlation between the years 1990 and 2013, showed a loss in the areas of primary vegetation of 5.37% and urban growth of 7.98%, in the comparison between the years 2017 and 2022, there was a loss in the area of primary vegetation of 2.97% and the urbanized area a growth of 1.97%, data that show that human activities have contributed to progressive deforestation on the island over the decades.